Enhancing Material Efficiency in Ship Production: A Taguchi Method Approach to Optimal Plate Nesting - Eko Prayetno; Firman Apriansyah; Djuan Sama Lewa (International Journal of Marine Engineering Innovation and Research, 2025)
This study seeks to enhance material use efficiency in plate nesting procedures for tugboat production through the application of the Taguchi method. Three critical criteria were assessed: plate profile dimensions, cutting margin, and number of parts, aimed at reducing material waste in steel plate cutting processes. Numerical simulations were performed with ProNest software, and the nesting output data were examined using Minitab to ascertain the ideal design via the Smaller-the-Better methodology. Experimental findings indicate that the ideal parameter configuration was attained with a plate profile dimension of 508 mm, a cutting margin of 10 mm, and a production quantity of 95 units. This setup resulted in little material waste, demonstrated by a maximum Signal-to-Noise Ratio (SNR) value of -49.17 dB, which is nearly zero. These findings indicate that this parameter combination can serve as a benchmark in production processes to improve material efficiency and minimize waste in tugboat fabrication.